Beyond news and rumours: political economy of kidnapping and insecurity in Nigeria - Omotola, J. Shola (The political economy of kidnapping and insecurity in Nigeria, 2024)
Cases of kidnapping and missing person have become too common in daily news, rumours and gossips in Nigeria. The fear of kidnapping has practically become the begging of wisdom in the country. It is against this background that this volume seeks to understand the phenomenon of kidnapping in Nigeria beyond the news and rumours of forceful disappearance and missing persons. Accordingly, this chapter provides an introductory insight into the political economy of kidnapping and the attendant security concerns. The subject matter is situated in the contexts of post/neo-colonial contradictions, state failure/weaknesses, neo/patrimonialism, democratic contradictions, competition for power and scarce resources, cost and benefits, frustration and aggression, greed and grievances, among other relevant political economy perspectives.